Orange-fleshed sweetpotato for nutrition and income-sub-Saharan Africa. Project profile. - International Potato Center (International Potato Center, 2019)
Sweetpotatoes, particularly the orange-fleshed varieties, have unexploited potential to contribute to nutritional and economic wellbeing in sub-Saharan Africa. This project will increase sweetpotato productivity and incomes on a large scale, benefiting farmers, processors and consumers, while also creating new job opportunities.